THE PROCESS OF DECENTRALIZATION AND ITS IMPACT ON LOCAL SELF-GOVERNANCE - Arben Ristemi (Journal of Bio-Based Marketing)
The process of decentralization in the Republic of North Macedonia is an important step towards strengthening local government and distributing political, economic, and social resources across the country. The decentralization period began in 2005 with amendments to the Constitution of the Republic of Macedonia and other legal provisions that created a framework for redistributing powers, resources, and responsibilities from the central government to local governments. The goal of the decentralization process is to ensure greater autonomy for local authorities, enable more efficient resource management, and increase the effectiveness of public services. However, as practice shows, this process also brings numerous challenges, such as a lack of financial resources, insufficiently trained personnel, and inadequate coordination between different levels of government. This paper aims to examine the decentralization process in the Republic of North Macedonia, with a particular focus on its impact on local government, the problems and challenges faced by municipalities, and the changes in legal and institutional frameworks.